2015
DOI: 10.1371/journal.pone.0134129
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Legacy of the Transatlantic Slave Trade in the Yungas Valley of Bolivia

Abstract: During the period of the Transatlantic Slave Trade (TAST) some enslaved Africans were forced to move to Upper Peru (nowadays Bolivia). At first they were sent to Potosí, but later to the tropical Yungas valley where the Spanish colonizers established a so-called “hacienda system” that was based on slave labor, including African-descendants. Due to their isolation, very little attention has been paid so far to ‘Afro-Bolivian’ communities either within the research field of TAST or in genetic population studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Other haplogroups present in the indigenous people are also observed in the modern population, including J2a2d, U6b1a and X3a. In line with previous analyses [27,31], a sub-Saharan African (L3d1b3a) [74] and an Amerindian lineage (A2) [75] are observed in the current population of the Canary Islands. Assuming that our set of 48 ancient genomes is representative of the native population, we performed a rough admixture estimate of 27.8% of maternal lineages in members of the present-day population possessing indigenous origins, while 61.1% would be of European ascription (Figure S3).…”
Section: Resultssupporting
confidence: 88%
“…Other haplogroups present in the indigenous people are also observed in the modern population, including J2a2d, U6b1a and X3a. In line with previous analyses [27,31], a sub-Saharan African (L3d1b3a) [74] and an Amerindian lineage (A2) [75] are observed in the current population of the Canary Islands. Assuming that our set of 48 ancient genomes is representative of the native population, we performed a rough admixture estimate of 27.8% of maternal lineages in members of the present-day population possessing indigenous origins, while 61.1% would be of European ascription (Figure S3).…”
Section: Resultssupporting
confidence: 88%
“…The map shows the great fit between archaeological and mtDNA evidence, then suggesting that B2 is a good marker of the demographic transformation occurring in the Andes. The highest frequencies of B2 in South America are by far in the Andean regions of Peru, Bolivia, and northern Argentina, reaching frequencies up to 70%-90% in some Aymara and Quechua Andean populations (Bert et al 2001;Barbieri et al 2011;Heinz et al 2013Heinz et al , 2015. The pre-Columbian mtDNA data available follow the same pattern: B2 reaches high frequencies in the Peruvian highlands, ranging from 42% to 75% (Shinoda et al 2006;Baca et al 2012Baca et al , 2014.…”
Section: Discussionmentioning
confidence: 75%
“…Stimulated by the recent findings of Heinz et al [ 33 ] indicating the presence of mtDNA East African ancestry in the Yungas region, we tested for this ancestry in the autosomal genome of the two ‘Afro-Bolivians’ analyzed in the present study. In this regard, exploratory ADMIXTURE analysis suggested that the Luhya could, at least in part, explain the East African component observed in the Tocaña.…”
Section: Discussionmentioning
confidence: 99%
“…A collection of 105 saliva samples recruited from the Yunga’s region of Bolivia was previously characterized for mtDNA and a panel of Ancestry Informative Markers or AIMs [ 33 ]. A small subset of these samples was additionally analyzed for a selection of Y-chromosome markers [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation